Comparison of DMSP cross-track ion drifts and SuperDARN line-of-sight velocities - R. A. Drayton; A. V. Koustov; M. R. Hairston; J.-P. Villain (Annales Geophysicae, 2005)
Cross-track ion drifts measured by the DMSP satellites are compared with line-of-sight SuperDARN HF velocities in approximately the same directions. Good overall agreement is found for a data set comprising of 209 satellite passes over the field of view of nine SuperDARN radars in both the Northern and Southern Hemispheres. The slope of the best linear fit line relating the SuperDARN and DMSP velocities is of the order of 0.7 with a tendency for SuperDARN velocities to be smaller. The agreement implies that the satellite and radar data can be merged into a common set provided that spatial and temporal variations of the velocity as measured by both instruments are smooth. Keywords. Ionosphere (Ionospheric irregularities; Plasma convection; Auroral ionosphere)